Government Reward-Penalty Mechanism in Closed-Loop Supply Chain Based on Dynamics Game Theory - Xiaoqing Zhang; Yingsheng Su; Xigang Yuan (Discrete Dynamics in Nature and Society)
The paper discusses the government reward-penalty mechanism (RPM) between two competing manufacturers and a recycler in closed-loop supply chain (CLSC) under asymmetric information. According to the dynamics game theory and principal-agent theory, three decision-making models are built: (1) decentralized dynamics game model without RPM, (2) decentralized dynamics game model with carbon emission RPM, and (3) decentralized dynamics game model with carbon emission RPM and recovery ratio RPM. The results show that (1) the carbon emission RPM increases product sale price, while it decreases the WEEE buy-back price and the WEEE recovery ratio, besides the profit of recycler. To some extent, it cannot motivate WEEE recycling. (2) Recovery ratio RPM improves the WEEE recovery ratio and lowers the product sale price; it also benefits manufacturer-1’s and recycler’s profits and consumers’ surplus. So it strongly proved effectiveness in guiding WEEE recycling. (3) In any case, the product sale price of manufacture-1 is lower than that of manufacturer-2. Similarly, the WEEE buy-back price and WEEE recovery ratio with H type are higher than those of L type, respectively. Apparently, it is suggested that the manufacturer participating in WEEE recycling and remanufacturing can gain competitive advantages; meanwhile, the recycler with high fixed cost has the scale advantages. (4) The competition can benefit improving WEEE recovery ratio. A numerical simulation is given to examine the theoretical results. According to the main conclusions, we propose that taking active part in recycling and remanufacturing WEEE and choosing the recycler with high fixed cost to cooperate are the wise choices for manufacturers. The recycler should expand fixed recovery cost investment, which will contribute to getting the scale effect; the government needs to balance the carbon emission RPM and recovery ratio RPM so as to cut down environmental pollution and guide the CLSC into WEEE recycling and remanufacturing. The most important carbon emission reward-penalty intensity should be set appropriately in case of discouraging members of CLSC recycling WEEE.